2009
DOI: 10.4236/jwarp.2009.12014
|View full text |Cite
|
Sign up to set email alerts
|

Remove of Phenolic Compounds in Water by Low-Temperature Plasma: A Review of Current Research

Abstract: Phenolic compounds have very strong toxicity, so it has been paid sharply attention to find an effective way of controlling the wastewater containing phenolic compounds. The work on this subject done by domestic and overseas scholars is studied in this paper, and the progress of researches on low-temperature plasma treatment is summarized through the electrical discharge types, mechanism, kinetics of phenolic compounds decomposition and combination of several methods with low-temperature plasma treatment. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Due to diffusion processes and the extent of the oxidizing species, such as • OH, • O, O 3 , are finally dissolved in the liquid phase (seefigure 8), these species could promote chemical reactions in the liquid phase to generate other reactive species, as noted by other authors[21,22] …”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Due to diffusion processes and the extent of the oxidizing species, such as • OH, • O, O 3 , are finally dissolved in the liquid phase (seefigure 8), these species could promote chemical reactions in the liquid phase to generate other reactive species, as noted by other authors[21,22] …”
mentioning
confidence: 86%
“…ozone formation, (2) it prevents the production of unwanted chemical species such as nitrogen oxides, which can affect the oxidation of pollutants. It has been found that the presence of nitrogen in the gas mixture strongly decreases the rate of degradation of phenol; substituted phenols [22] and inorganic acids [28] can also be generated.…”
Section: Phenol Oxidationmentioning
confidence: 99%
“…The detection of phenolic compounds in food, medical, environmental ground, and surface water has been a key issue because of the respective toxicity and persistency in the environment. 103 Some phenol derivatives are from industrial waste due to their use as intermediates in the production drugs, explosives, wood preservatives, and in leather treatments. These polluting chemicals are readily adsorbed by the skin and mucous membrane of human and animal.…”
Section: Malathion (Mlt)mentioning
confidence: 99%
“…In this gas phase oxidizing species such as · OH, · 0 and 03 are generated by means of the following reactions [6] e + O2 � e + · 0 + · 0 H20 ( aq ) � H20 (g) e + H20 (g) � · OH + · H + e 0+ H20 (g) � · OH + · OH · 0 + O2 + O2 � 03 + O2 e + Ar � Ar* + e Ar* + O2 � Ar + · 0 + · 0 Due to diffusion processes, oxidizing gas species such as · OH, · 0, 03, go to the liquid phase. In the aqueous phase the following reactions are carried out [7,8], which are promoted by the species and/or UV radiation generated previously in the gas phase: 03 (g) � 03 ( aq ) H20 + 03 � · OH + · OH + O2 · H + · 0 + · 0 � H02 The presence of aqueous electrons in the solution is generally function of the type of applied electric power, that is DC or AC [4], in general the presence of aqueous electrons is justified when DC pulsed systems and sharp tips under the water are used to generate nonthermal plasma. In this case an AC system was used and the aqueous electrons were not considered.…”
Section: B Chemical-kineticsmentioning
confidence: 99%